Quantitative analysis of glyphosate, glufosinate and AMPA in irrigation water by in situ derivatization–dispersive liquid–liquid microextraction combined with UPLC-MS/MS - Pinto, Edgar; Soares, António Gomes; Ferreira, Isabel M. P. L. V. O. (Analytical methods, 2018)
A novel method was developed for the sensitive, cheap and fast quantitation of glyphosate, glufosinate and aminomethylphosphonic acid (AMPA) in irrigation water by in situ derivatization and dispersive liquid–liquid microextraction (DLLME) combined with ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). Water samples were filtered with a 0.22 μm nylon filter, pH adjusted to 9 with ammonium bicarbonate and derivatized with fluorenylmethyloxycarbonyl chloride (FMOC-Cl). Afterwards, DLLME was applied to concentrate the compounds of interest, which were then analyzed by UPLC-MS/MS. The best results were obtained when acetone and dichloromethane were used as dispersive and extraction solvents, respectively. Two-level full factorial designs and a central composite design were applied to select the most appropriate derivatization and DLLME conditions. The method performance was evaluated according to the SANTE/11945/2015 guidelines and was linear in the 1.0 to 200 μg L −1 range for glyphosate, glufosinate and AMPA, with r 2 ≥ 0.997 and individual residuals <13%. Repeatability (RSD r ) and within-laboratory reproducibility (RSD wr ) ranged from 2.7 to 9.1% and from 3.4 to 14.3%, respectively, and the trueness between 94.9 and 118.1%. The limits of detection were 0.35, 0.05 and 0.10 μg L −1 for glyphosate, glufosinate and AMPA, respectively and the limit of quantitation was 1.0 μg L −1 for all three compounds. The developed method was successfully applied to the analysis of irrigation water (surface and groundwater). No sign of the three compounds was detected in the groundwater samples but glyphosate was quantified in surface waters.